Pedagogical study on the effect of the holy month of Ramadan on the volume of operations and abnormal returns in the Iranian capital market - Noori, Abdollah (2020)
The objective of this study was to evaluate the calendar effect of the holy month of Ramadan on trading volume and abnormal returns in the Iranian capital market during the years 2009 to 2019 for 10 years in the stock exchange. The present study is considered as applied in terms of purpose and correlation in terms of descriptive method. Also, the data panel model was used to investigate the relationship between the variables. According to the results, the variable coefficient of the effect of the holy month of Ramadan on the trading volume has a significant level of 0.441, therefore, considering that this value is greater than the alpha level of the research, which is equal to 0.05, therefore, this hypothesis (zero) that the variable of the effect of Ramadan is not effective on the variable of trading volume, is not rejected. Therefore, the effect of the calendar of the holy month on the volume of transactions is not significant. Also, variable coefficient of the effect of Ramadan and the share return has a significant level of 0.000, so considering that this value is smaller than the alpha level of the research, which is equal to 0.05, therefore, this hypothesis (zero) that the variable of Ramadan effect D01 does not affect the share return in Iran, is rejected.